Experimental investigation on the performance of a neon cryogenic oscillating heat pipe. (June 2017) - Liang, Qing; Li, Yi; Wang, Qiuliang
Highlights: The cooling down process of the neon cryogenic OHP from room temperature is studied. The operation characteristics at the working temperature are analyzed. Effects of the heat input and filling ratio on the thermal performance are discussed. The effective thermal conductivity is 6100–22, 180 W/m K for 24.5% filling ratio. Abstract: An experimental investigation is conducted to study the performance of a cryogenic oscillating heat pipe (OHP) using neon as the working fluid. The stainless steel OHP with an inner diameter of 0.9 mm has 4 turns, and the lengths of the evaporator, condenser section and adiabatic section are 35 mm, 35 mm and 95 mm, respectively. The temperature of the evaporator and condenser and the pressure of the OHP are measured. The results show that the cooling down process of the OHP from room temperature to the working temperature can be significantly accelerated by charging with neon. During the pseudo steady-state operation process, the temperature of evaporator and the pressure of the OHP increase with increasing heat input. When the dry out appears, the temperature of evaporator rises quickly, and the pressure of the OHP drops sharply. In addition, the effective thermal conductivity of the OHP at the different heat inputs and the different filling ratios is calculated. It increases with increasing heat input, and there exists an optimum filling ratio which makes the maximum effective thermal conductivity. For this OHP, the optimum filling ratio is 24.5%, at which the effective thermal conductivity is 6100–22, 180 W/m K.